UPAYA MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV PADA MATERI KEGIATAN JUAL BELI MELALUI PENGGUNAAN METODE DEMONSTRASI DENGAN BANTUAN MEDIA DIORAMA DI SDN METESIH 03 KABUPATEN MADIUN - Alyatiko Salsabila; Syahda Nur Fadilah; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The process of acquiring knowledge regarding buying and selling activities is facilitated through demonstration methods, utilizing diorama media to enhance student learning outcomes and aid students in comprehending the instructional material presented in class IV at SDN Metesih 03 in Madiun Regency. This research was executed employing classroom action research techniques, which were conducted in two phases: the pre-cycle and cycle one. The participants in this study were fourth-grade students from SDN Metesih 03, totaling 8 students. Data collection was performed through observation and written assessments of the students. Consequently, all collected data was analyzed by: 1) reviewing the research data, 2) calculating the results obtained, 3) presenting the data findings, and 4) drawing conclusions from the research results. The findings indicated that after implementing role-playing, 7 out of 8 students successfully completed the learning objectives in the pre-cycle test. In cycle II, with the enhancement of learning through the application of diorama media, all 8 students achieved completion of the learning objectives. Thus, the students' ability to grasp the material related to buying and selling activities improved significantly from pre-cycle to cycle I, with an average understanding increasing from 92.5 to 95.